2019
DOI: 10.17309/tmfv.2019.4.02
|View full text |Cite
|
Sign up to set email alerts
|

Research Program: Modeling of Young Gymnasts’ Training Process

Abstract: The study purpose was to substantiate theoretical and methodological grounds and the concept of a research program of the training process based on modeling of individual components of the young gymnasts’ training system.  Materials and methods. The study involved: 30 gymnasts – 3rd senior category, 30 gymnasts – 2nd senior category, 26 gymnasts – 1st senior category. Young gymnasts participating in the experiment received athletic titles from the 1st category to master of sports (1st c. – 18 persons, CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 15 publications
4
17
0
3
Order By: Relevance
“…Among the objects studied using mathematical modeling in physical education are: age dynamics of children's functional and motor fitness; physical exercises modes and their impact on performance; children's motor training. A 2k full factorial experiment (models of training effects), logistic function (determination of terms of teaching and motor abilities development), and discriminant function (pedagogical control of fitness level) can be used to obtain the models (Lopatiev, Ivashchenko, Khudolii, Pjanylo, Chernenko, & Yermakova, 2017;Ivashchenko, 2016;Khudolii, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Among the objects studied using mathematical modeling in physical education are: age dynamics of children's functional and motor fitness; physical exercises modes and their impact on performance; children's motor training. A 2k full factorial experiment (models of training effects), logistic function (determination of terms of teaching and motor abilities development), and discriminant function (pedagogical control of fitness level) can be used to obtain the models (Lopatiev, Ivashchenko, Khudolii, Pjanylo, Chernenko, & Yermakova, 2017;Ivashchenko, 2016;Khudolii, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The obtained results specify the conceptual approaches to experiment planning in studying the effectiveness of children's physical education, factorial designs are an objective tool for obtaining data to calculate regression models of training effects in children (Khudolii, Ivashchenko, Iermakov, Nosko, & Marchenko, 2019;Khudolii, 2019;Ivashchenko, 2020).…”
Section: Regression Equationsmentioning
confidence: 87%
“…Researchers pay special attention to: • substantiating the amount of motor activity (Kondakov, Voloshina, Kopeikina, & Kadutskaya, 2020;Bueichekú, Ávila, Miró-Padilla, & Sepulcre, 2019;Lothmann, Holmes, Chan, & Lau, 2011); • studying the influence of motor activity on cognitive functions (De Bruijn, Kostons, Van Der Fels, Visscher, Oosterlaan, Hartman, & Bosker, 2020;Haverkamp et al, 2020); • learning technologies (Ivashchenko, Iermakov, Khudolii, Cretu, & Potop, 2017;Ivashchenko & Kapkan, 2015;Khudolii, Kapkan, Harkusha, Marchenko, & Veremeenko, 2020); • technologies of motor abilities development (Iermakov, Ivashchenko, Khudolii, & Chernenko, 2020;Ivashchenko, Khudolii, Prusik, & Giovanis, 2020;Ivashchenko, Nosko, & Ferents, 2019). The integrity of the educational process in physical education and sport was considered by Khudolii (2019), Ivashchenko (2020), Khudolii, Iermakov, and Bartik (2020). It was found that the positive effect of learning depends on consistent solving of learning problems and rational application of methods.…”
Section: Introductionmentioning
confidence: 99%